The Lost Promise of Democratic Socialism in Russia. Issue 2 (3rd April 2017) - Klimina, Anna
Abstract: To explain the failure to create democratic socialism in Russia after the 1917 Bolshevik Revolution, I apply Thorstein Veblen's vision of economic democracy as a cure for vested interests. In late imperial Russia, many socialist thinkers imagined socialism primarily in terms of workplace democracy, worker ownership, local governance, and economic decentralization. Their vision was destroyed, first, by Bolshevik policies and then by Stalin's tyrannical command economy. Thereafter, vested interests reemerged in the Soviet Union as an underground economy, rife with theft of public resources, and then, with the beginning of transition, capitalism in its most neoliberal form was restored.